1985
DOI: 10.1080/09553008514550051
|View full text |Cite
|
Sign up to set email alerts
|

Heat-induced Alterations in DNA Polymerase Activity of HeLa Cells and of Isolated Nuclei. Relation to Cell Survival

Abstract: The activity of DNA polymerase alpha and beta was assayed in heated HeLa S3 cells as well as in nuclei isolated from these cells. The enzyme activity as measured in cells and in nuclei has been compared with the extent of cell survival after the different hyperthermic doses. It was found that although the activity of the cellular DNA polymerases was related to cell survival after single heat doses, no correlation was found when thermotolerant cells were heated. When the activity of the DNA polymerases was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
21
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 17 publications
(11 reference statements)
3
21
0
1
Order By: Relevance
“…It has been shown previously by us (Kampinga et al, 1985(Kampinga et al, , 1987(Kampinga et al, , 1989b and other investigators (Warters and Roti Roti, 1982;Roti Roti and Wilson, 1984;Higashikubo et al, 1986;McConnell et al, 1987) that hyperthermic treatment of cells increases the protein mass of nuclei isolated from these heated cells (TX-100 insoluble fraction). This is most likely due to an intranuclear protein aggregation as a result of the heat treatment (Kampinga et al, 1985(Kampinga et al, ,1987(Kampinga et al, ,1989bMcConnell et al, 1987).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…It has been shown previously by us (Kampinga et al, 1985(Kampinga et al, , 1987(Kampinga et al, , 1989b and other investigators (Warters and Roti Roti, 1982;Roti Roti and Wilson, 1984;Higashikubo et al, 1986;McConnell et al, 1987) that hyperthermic treatment of cells increases the protein mass of nuclei isolated from these heated cells (TX-100 insoluble fraction). This is most likely due to an intranuclear protein aggregation as a result of the heat treatment (Kampinga et al, 1985(Kampinga et al, ,1987(Kampinga et al, ,1989bMcConnell et al, 1987).…”
Section: Resultsmentioning
confidence: 83%
“…This is most likely due to an intranuclear protein aggregation as a result of the heat treatment (Kampinga et al, 1985(Kampinga et al, ,1987(Kampinga et al, ,1989bMcConnell et al, 1987). It has been shown that such changes may be related to thermal cell killing, also for conditions of heat-induced thermotolerance (Kampinga et al, 1987, 198913).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This has been suggested to play a role in cell survival, DNA synthesis and repair, and transcription [Kampinga et al, 1985;Roti Roti and Laszlo, 1988;Fisher, 1990]. Recent studies have clearly documented that changes in the nuclear proteins in response to heat shock are significantly reflected in the nuclear matrix, and further, the modifications in the association of specific proteins with the nuclear matrix is of a differential nature [VanderWaal et al, 1996, Roti Roti et al, 1998].…”
mentioning
confidence: 97%
“…There is uncertainty, however, as to how much of the increase in nuclear protein content of nuclei isolated from heated cells is due to cytoplasmic proteins moving into the nucleus, adsorption of cytoplasmic proteins to nuclei during their isolation, and less extraction of nuclear proteins during the nuclear isolation procedure. For example, much of the activity of DNA polymerase a and p, almost exclusively nuclear enzymes (Bensch et al, 19831, is lost from the nuclei during their isolation, but this loss is greatly reduced if the cells are heated prior to isolation of the nuclei (Kampinga et al, 1985; also our unpublished data). Heat would be expected to reduce the loss of activity of nuclear enzymes during isolation of nuclei, if heat caused an increase in the binding or trapping of proteins within nuclear components.…”
mentioning
confidence: 85%